Antioxidant Properties of Protein-Rich Plant Foods in Gastrointestinal Digestion-Peanuts as Our Antioxidant Friend or Foe in Allergies - Ivana Prodić; Maja Krstić Ristivojević; Katarina Smiljanić (MDPI AG, 2023)
Thermally processed peanuts are ideal plant models for studying the relationship between allergenicity and antioxidant capacity of protein-rich foods, besides lipids, carbohydrates and phytochemicals. Peanut is highly praised in the human diet; however, it is rich in allergens (>75% of total proteins). One-third of peanut allergens belong to the products of genes responsible for the defence of plants against stress conditions. The proximate composition of major peanut macromolecules and polyphenols is reviewed, focusing on the identity and relative abundance of all peanut proteins derived from recent proteomic studies. The importance of thermal processing, gastrointestinal digestion (performed by INFOGEST protocol) and their influence on allergenicity and antioxidant properties of protein-rich plant food matrices is elaborated. Antioxidant properties of bioactive peptides from nuts were also considered. Moreover, there are no studies dealing simultaneously with the antioxidant and allergenic properties of protein- and polyphenol-rich foods, considering all the molecules that can significantly contribute to the antioxidant capacity during and after gastrointestinal digestion. In summary, proteins and carbohydrates are underappreciated sources of antioxidant power released during the gastrointestinal digestion of protein-rich plant foods, and it is crucial to decipher their antioxidant contribution in addition to polyphenols and vitamins before and after gastrointestinal digestion.